2010
DOI: 10.1590/s0004-282x2010000600010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal meningitis according to the microbiological diagnosis: a decade of experience in a tertiary center

Abstract: The aim of this study was to evaluate the incidence of and mortality due to meningitis and compare data according to microbiological diagnosis. This was a ten-year retrospective study conducted at a neonatal intensive care unit (NICU). Newborns with meningitis confirmed by positive CSF culture were included; those with congenital infection or malformations that made lumbar puncture impossible were excluded. The variables investigated were birth weight, gestational and postnatal age, procedures, hematological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
19
0
5
Order By: Relevance
“…The prevalence of meningitis in our NICU was 0.7% which is comparable to study by Bentlin et al (0.6%). 17 The study from Africa and Asia reported incidence of meningitis ranging from 0.8 to 6.1 per 1000 live births. 18 Neonatal risk factors observed in our study were low birth weight (87.7%), prematurity (75%), birth asphyxia (20.1%), mechanical ventilation (17.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of meningitis in our NICU was 0.7% which is comparable to study by Bentlin et al (0.6%). 17 The study from Africa and Asia reported incidence of meningitis ranging from 0.8 to 6.1 per 1000 live births. 18 Neonatal risk factors observed in our study were low birth weight (87.7%), prematurity (75%), birth asphyxia (20.1%), mechanical ventilation (17.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Bentlin et al have also reported (21 out of 22) late onset of neonatal meningitis cases. 17 These low rates of positive culture in early infection may be due to hemodynamic instability which delays lumbar puncture and use of antibiotics before the lumbar puncture which interfere with bacterial growth. 34 The Out of the 20 isolates of K. pneumoniae, 9 (45%) isolates were ESBL producers.…”
Section: Discussionmentioning
confidence: 99%
“…El aumento se relacionaría con una mejora en el diagnóstico, mayor complejidad asistencial y mejor capacidad resolutiva. Sin embargo, se encuentra dentro del rango esperado a nivel internacional (3,10,13,14) .…”
Section: Discussionunclassified
“…La tasa de letalidad fue menor a la esperada para países en desarrollo (15-30%) y es concordante con países desarrollados (<10%) (5,9,14) , siendo mayor en casos de MN temprana. Esto difiere de estudios españoles y franceses donde se encontraron tasas de letalidad de 2,3 y 2 veces mayor en MN tardía, teniendo ambos mayores tamaños poblacionales (10,17) .…”
Section: Discussionunclassified
“…Thus, ataxic mice had histological changes characteristic of Gram-negative bacillary meningoencephalitis. 21 Fluorescence immunohistochemistry and confocal microscopy revealed that the severe histological changes in the ataxic Nramp1 þ/þ mice were associated with areas of bacterial infection. Salmonella was observed in the olfactory bulb ( Figure 9A), periventricular areas ( Figure 9B), ventricles ( Figure 9, C and D), and meninges ( Figure 9, E and F).…”
Section: Pathology Correlates With Neurological Signs Of Ataxia In Nrmentioning
confidence: 96%